Vitamin D Deficiency as Etiological Factor for Breast Cancer - Maleeha Tahir Butt, Amber Shami, Waqas Qarshi, Raheela Shaheen, Zarrin Khaliq Chaudari, Mehak Shafiq, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine the association between vitamin D deficiency and breast cancer. Material and methods: This study was conducted on 72 participants, 36 cases and 36 healthy controls were enrolled. Basic demographic information was recorded. Vitamins D deficiency was assessed between both groups. Serum Vitamin D level < 20 ng/ml was considered as vitamin D deficient. Results: Mean age in the cases was 34.64±9.14 years and 36.22±8.78 years in controls. Significant association was found between vitamins D deficiency and breast cancer. In cases there 28 (77.7%) patients with vitamin D deficient and in controls 15 (41.7%) patients. Conclusion: Vitamin D deficiency is a major risk factor for breast cancer.